The Influence of Brand Image and Brand Love on Customer Loyalty with Customer Engagement as an Intervening Variable on Consumers Somethinc Brand at Delipark Mall Medan - Hartini Pratiwi Pane; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of study This is For analyze in a way direct and indirect direct Influence Brand Image and Brand Love Towards Customer Loyalty With Customer Engagement As An Intervening Variable On Somethinc Brand Consumers at Delipark Mall Medan . Population​ in study This is all over consumer Somethinc brand at Delipark Mall Medan with amount population that is not known with sure . Technique in taking sample in study This is use technique taking sample with method nonprobability sampling with technique purposive sampling . Purposive sampling is technique taking sample based on consideration​ certain . The data analysis method used is SEM-PLS. In research This consists of from 2 variables independent variable , 1 intervening variable , and 1 dependent variable bound . Total statement in study This is 32 statements , so the minimum size is sample study This is 32 x 5 = 160, so amount sample taken​ in study This is 160 respondents . The results of the study show that variable brand image and brand love in a way direct influential significant to customer engagement, variable brand image in a way direct No influential significant to customer loyalty , brand love in a way direct influential significant to customer loyalty, furthermore customer engagement in a way direct influential significant to customer loyalty , brand image in a way No direct influential significant to customer loyalty through customer engagement , as well as variable brand love in a way No direct influential significant to customer loyalty through customer engagemen.